Quality Improvement Management of Madrasahs and the Competitiveness of Islamic Educational Institutions at Madrasah Aliyah Negeri 3 Palembang - Kurnia, Riza; Zainuri, Ahmad; Yasir, Muslim Gani (The Future of Education Journal, 2025)
This study aims to analyze the quality improvement management strategies implemented at State Islamic Senior High School (MAN) 3 Palembang in order to improve competitiveness as an Islamic educational institution. Using a qualitative descriptive approach, this study explores the efforts made by the management of the madrasah in improving the quality of educational services, the performance of teaching staff, and student learning outcomes. The results of the study indicate that MAN 3 Palembang implements various quality improvement strategies, such as continuous teacher competency development, strengthening Islamic work culture, and implementing a data-based evaluation system. In addition, the synergy between the head of the madrasah, teachers, students, and parents is also an important factor in creating a superior and competitive learning environment. This quality improvement also has a direct impact on the positive image of the madrasah in the eyes of the community and strengthens its position in the competition between educational institutions in the Palembang area. This study confirms that planned and participatory quality management can be the main key in realizing an excellent and highly competitive Islamic educational institution